THE DIGITAL LIBRARIAN A DIGITAL ASSISTANCE FOR THE LIBRARIAN USING VISUAL BASIC AND GSM TECHNOLOGY - Bhatia, Mihal; Chandura, Raj; Gade, Rajesh; Kale, Tushar; Shukla, Ashish; Awathankar, Rahul.V. (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
The Digital librarian is a system which can be used to reduce the work load of a librarian to bare minimum. The proposed consists of various sections which helps the librarian incarrying out the tasks. A GSM module is used in this system, all the communications between the librarian and the students are done by the GSM module. The database stored on the PC is accessed by a VB program. The Students send an SMS to the GSM module requesting the desired book, theVB program verifies the authentication of the student and checks the availability of the book. If thebook is available, the book is issued to the respective student, the student will receive a confirmationSMS and request to collect the book from the librarian. In case the book is not available the student will be kept on HOLD and when a book is submitted, the system will respond to the waiting student and wait for the reply from the student to send an acknowledging message.